Implications of Digitalization on Governance at Islamic People's Bank: Phenomenological Study at BPRS X - Yulianti, Neneng Ina; Yuhertiana, Indrawati; Sundari , Siti (PT. Maju Malaqbi Makkarana, 2025)
Digital transformation at Islamic Rural Banks demands governance that is accountable, secure, and aligned with sharia principles. This study aims to map digital governance practices and formulate prerequisites for safe, compliant, and value-oriented implementation. Using a qualitative phenomenological approach and adopting an active participatory method, data were collected through in-depth interviews, document reviews, and observations with purposive sampling (management, DPS, IT/cybersecurity units, and customers). The analysis refers to the Miles & Huberman model (data reduction–data presentation–conclusion drawing); validity is maintained through source triangulation, member checking, and audit trails. The findings consolidate five key domains: (1) the role of DPS in digital decisions and ongoing supervision, (2) human resource capabilities and risk culture, (3) IT & cybersecurity architecture (data protection, incident response, business continuity), (4) risk management–compliance (synchronization of OJK–DSN–MUI guidelines), and (5) digital customer literacy and experience. The theoretical contribution integrates the Institutional, Accountability, and TAM/UTAUT perspectives to explain the drivers and barriers to adoption. Practically, a risk-based digital governance roadmap is developed that prioritizes cybersecurity governance, strengthening the role of the DPS through digital oversight, and data governance policies.